2023
DOI: 10.3389/fendo.2022.1072176
|View full text |Cite
|
Sign up to set email alerts
|

Correlation study of male semen parameters and embryo aneuploidy in preimplantation genetic testing for aneuploidy

Abstract: ObjectiveThe purpose of this study was to evaluate the influence of abnormal semen parameters on embryo aneuploidy based on single nucleotide polymorphism microarray (SNP array).MethodsA total of 464 blastocysts from 103 PGT-A cycles were analyzed. The embryo quality and embryo aneuploidy rates were compared between different groups which divided by male semen parameters (sperm concentration, motility, morphology, and DFI) according the WHO criteria (2021).ResultsThe total blastocysts chromosome aneuploidy rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…However, since leukocytospermia has been linked to increased DNA fragmentation, directly testing for DNA fragmentation prior to IVF treatment may be more helpful. Several studies have suggested a link between higher sperm DNA fragmentation and blastocyst aneuploidy rate [ 22 , 23 ]. In our study, the aneuploidy rate was slightly higher in the leukocytospermia group but did not reach significance.…”
Section: Discussionmentioning
confidence: 99%
“…However, since leukocytospermia has been linked to increased DNA fragmentation, directly testing for DNA fragmentation prior to IVF treatment may be more helpful. Several studies have suggested a link between higher sperm DNA fragmentation and blastocyst aneuploidy rate [ 22 , 23 ]. In our study, the aneuploidy rate was slightly higher in the leukocytospermia group but did not reach significance.…”
Section: Discussionmentioning
confidence: 99%
“…[7] The abnormal expression of sperm-specific nuclear proteins or their association with chromatin can alter sperm chromatin structure and affect sperm function. [8,9] In the 6th edition of the WHO manual for human semen analysis, sperm DNA fragmentation, sperm chromatin, sperm aneuploidy, and semen interleukin have been added.…”
Section: Introductionmentioning
confidence: 99%